Stimulation of dihydroxyacetone and glycerol kinase activity in Streptococcus faecalis by phosphoenolpyruvate-dependent phosphorylation catalyzed by enzyme I and HPr of the phosphotransferase system. - Deutscher, J (1986)
Recently we reported the phosphoenolpyruvate (PEP)-dependent phosphorylation of a 55-kilodalton protein of Streptococcus faecalis catalyzed by enzyme I and histidine-containing protein (HPr) of the phosphotransferase system (J. Deutscher, FEMS Microbiol. Lett. 29:237-243, 1985). The purified 55-kilodalton protein was found to exhibit dihydroxyacetone kinase activity. Glycerol was six times more slowly phosphorylated than dihydroxyacetone. The Kms were found to be 0.7 mM for ATP, 0.45 mM for dihydroxyacetone, and 0.9 mM for glycerol. PEP-dependent phosphorylation of dihydroxyacetone kinase stimulated phosphorylation of both substrates about 10-fold. Fructose 1,6-diphosphate at concentrations higher than 2 mM inhibited the activity of phosphorylated and unphosphorylated dihydroxyacetone kinase in a noncompetitive manner. The rate of PEP-dependent phosphorylation of dihydroxyacetone kinase was about 200-fold slower than the phosphorylation rate of III proteins (also called enzyme III or factor III), which so far have been considered the only phosphoryl acceptors of histidyl-phosphorylated HPr. P-Dihydroxyacetone kinase was found to be able to transfer its phosphoryl group in a backward reaction to HPr. Following [32P]PEP-dependent phosphorylation and tryptic digestion of dihydroxyacetone kinase, we isolated a labeled peptide composed of 37 amino acids, as determined by amino acid analysis. The single histidyl residue of this peptide most likely carries the phosphoryl group in phosphorylated dihydroxyacetone kinase.